The Influence of Social Media Marketing on Purchase Decision Through Brand Trust as an Intervening Variable - Salman, Intania Fernidella; Adhi Prasetyo (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
This study aims to analyze the influence of Wardah’s social media marketing efforts, specifically on Instagram, on purchase decisions, with brand trust as an intervening variable. This research employs a quantitative approach with a descriptive and causal design. Data were collected through surveys using structured questionnaires distributed to 416 Wardah consumers actively engaging with the brand’s social media. The analysis was conducted using Structural Equation Modeling (SEM) to examine the relationships between social media marketing, brand trust, and purchase decisions. The results indicate that social media marketing significantly influences purchase decisions, both directly and indirectly through brand trust. Among the dimensions studied, informativeness and interactivity play a stronger role in enhancing brand trust compared to perceived relevance. This study contributes to digital marketing literature by emphasizing the role of brand trust in strengthening the impact of social media marketing on purchase decisions. The findings provide valuable insights for businesses to optimize their digital marketing strategies through engaging and informative content.